Dissecting Disorder Perceptions: Neighborhood Structure and the Moderating Role of Interethnic Contact and Xenophobic Attitudes. (December 2022) - Janssen, Heleen J.; Oberwittler, Dietrich; Gerstner, Dominik
Although urban disorder has played a central role in neighborhood research, its impact may have been overstated in studies relying on the subjective perception of survey respondents only. Research on the "perception bias"—defined as the divergence between respondents' subjective assessments and systematic observations of disorder—has revealed the ambiguous nature of disorder and opened a door to the analysis of the social construction of this environmental cognition. Using survey and observational data from 140 small neighborhoods in two German cities, we advance this research by focusing on the moderating role of residents' interethnic contacts and attitudes. The results show that the effects of neighborhood minority concentration on the perception bias are conditional on the residents' interethnic contacts and xenophobic attitudes. These findings highlight the subjectivity of disorder perceptions and caution against a naive understanding of Broken Windows theory.